1987
DOI: 10.1097/00006842-198705000-00003
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal investigation of the relationships among alcohol consumption, psychosocial factors, and blood pressure.

Abstract: Although a number of studies have demonstrated a link between alcohol intake and blood pressure, virtually no research has examined this relationship or the relevance of psychosocial variables in this context over time. This study utilized data from 416 subjects in the Air Traffic Controller Health Change Study to track these associations across five examinations over a 3-year period. Following obesity, alcohol consumption was consistently the second-best predictor of blood pressure. Alcohol intake rose among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
3

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 27 publications
0
11
1
3
Order By: Relevance
“…Ressalte-se que, no presente trabalho, foi considerado etilista todo indivíduo que declarou ingerir álcool diariamente ou regularmente (mais de uma vez por semana), sem se levar em conta a quantidade ingerida. Há evidên-cias de que a ingestão de quantidades discretas de álcool produz um efeito protetor frente às dislipidemias, fato que, possivelmente, esteja influenciando os resultados do presente trabalho 3,6,9,14,17,36 .…”
Section: Resultsunclassified
“…Ressalte-se que, no presente trabalho, foi considerado etilista todo indivíduo que declarou ingerir álcool diariamente ou regularmente (mais de uma vez por semana), sem se levar em conta a quantidade ingerida. Há evidên-cias de que a ingestão de quantidades discretas de álcool produz um efeito protetor frente às dislipidemias, fato que, possivelmente, esteja influenciando os resultados do presente trabalho 3,6,9,14,17,36 .…”
Section: Resultsunclassified
“…With regard to the first concern, it is reported that increases in systolic and diastolic blood pressure were significantly greater in heavy drinkers. 1,11 Similarly, Nakanishi et al 12 examined 934 normotensive Japanese for 6 years and suggested that alcohol consumption was independently associated with hypertension. On the other hand, some studies have reported that baseline alcohol consumption is significantly associated with baseline blood pressure, but not with changes in blood pressure during the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…11,[14][15][16] The subjects in these studies consisted of both hypertensive and normotensive participants. In our study, we investigated only normotensive workers and found a significant association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No Município de São Paulo, a proporção de mortes por essas causas, foi de 37% 32 . Numerosos estudos demonstraram que na etiologia dessas doenças encontram-se fatores, cujas origens podem estar vinculadas às seguintes características: a) genéticas -propensão que o indivíduo já traz ao nascer, como herança familiar; b)-estilo de vida e qualidade de vida -modos de viver que conduzem a práticas, hábitos, pressões e desgaste físico-psicológico, que se constituem em fatores de risco, tais como tabagismo 36,47 , etilismo 6,8,11,13,15,17,23,47 , alimentação inadequada 1,3,7,18,19,20,21,22,25,26,33,35,37,39,41,45,46 , sedentarismo 31 , estresse físico e psicológico 12 e, entre as mulheres, uso de contraceptivos 9,31 . Devido à importância do tema, dada à crescente participação deste indicador de mortalidade na estatística vital, e à escassez de estudos pertinentes realizados no Brasil, foi proposto o Projeto Doenças Cardiovasculares Ateroscleróticas, Dislipidemias, Hipertensão, Obesidade e Diabetes Melito em População da Área Metropolitana de São Paulo (SP), que vem sendo desenvolvido pela Faculdade de Saúde Pública, Departamento de Nutrição, desde 1987.…”
Section: -Introduçãounclassified